Characteristics of At-Ta'lim, At-Tarbiyah, At-Ta'dib, At-Tadris, and At-Tazkiyah in the Qur'an. A Thematic and Epistemological Analysis Based on Primary and Classical Qur'anic Data - Ahmad Roni Maulana Setiawad; Ihwan Amalih (Penerbit Hellow Pustaka, 2026)
This article provides an in-depth academic analysis on five core educational concepts derived from the Qur’an at-ta‘lim, at-tarbiyah, at-ta’dib, at-tadris, and at-tazkiyah. Drawing exclusively from scriptural, linguistic, and classical sources, the study reveals that Qur’anic educational epistemology is at once divine (rabbaniyyah), holistic, gradual, ethical, transformative, and centered on the purification and elevation of the human soul. Through close analysis of the linguistic roots, Qur’anic verses, and classical commentaries (Rāghib al-Aṣfahānī, Ibn ‘Āshūr, al-Rāzī, al-Attas, al-Shawkānī), the article reconstructs a unified curriculum of Qur’anic pedagogy. The result demonstrates that these five terminologies are not isolated, but form an integrated system producing the ideal human being (al-insān al-rabbānī/al-kāmil).